Fruit injury in organic fruit production and its relationship to brown rot caused by Monilinia spp. - Abonyi, F.; Vámos, A.; Lakatos, P.; Rózsa, A.; Holb, I. J. (International Journal of Horticultural Science, 2016)
In a two-year Hungarian study, the temporal progress of brown rot incidence and various injury types were studied in organic fruit orchards and the relationship between brown rot and injury types was determined. Results showed that brown rot reached an almost 20% incidence level in both years. Total injury incidence reached up to 5.3 and 19.8% in the two years. In all cases, insect injury incidence was the highest among injury types in most assessment dates. Incidence levels of other injury types (bird injury, mechanical injury and other injury) began to increase, but none of those reached levels >4%. Pearson’s correlation coefficients showed that brown rot incidence correlated significantly with the incidence of insect injury. In addition, brown rot incidence and the incidence levels of bird injuries was also significantly correlated. High injury and brown rot incidence levels suggest further improvements on organic fruit protection.